Potential contributions of mammals to human well-being in Argentina - Alonso Roldán, Virginia (2022)
Mammals are key components of biodiversity mediating ecosystem functions, mainly because of the diversity of forms and functions of this group. Understanding and making explicit the role of mammals underpinning Nature's Contributions to People (NCP) or directly contributing to human well-being would help to influence policy formulation towards sustainable development and nature conservation. Through a workshop held at the XXXII Jornadas Argentinas de Mastozoología and subsequent collaborative work, we compiled information related to Mammal's Contributions to People in Argentina (MCP-Arg) based on participants' interpretation of the available literature and their field experience. Argentinian mammals contribute to 12 of the 18 defined NCPs. We derived numerous MCP-Arg from studies that focused mainly on ecological processes and conservation, revealing an information gap in MCP- Arg description, quantification, and mapping. All taxa contribute similarly to the overall contributions, highlighting the importance of preserving mammal diversity. Conservation should also be framed at the local community rather than regional scales, aiming to preserve ecological functioning and contributions to human well-being, especially within regulation contributions. Our results show destructive feedback between threats and habitat-related contributions, with habitat degradation being the greatest threat to mammalian contributions and habitat maintenance the most threatened one. Our research indicates that a substantial amount of knowledge about MCP-Arg is available through narratives and interpretations. Considering the NCP approach to mammalian research, we can make significant contributions to both mammal conservation and human well-being.